Weak Solutions for a Second Order Dirichlet Boundary Value Problem on Time Scale - Wandong Lou (Journal of Applied Mathematics)
We adopt the Leray-Schauder degree theory and critical point theory to consider a second order Dirichlet boundary value problem on time scales and obtain some existence theorems of weak solutions for the previous problem.